Approach to evaluating health level and adaptation possibilities in schoolchildren - Andrieieva, O.V.; Sainchuk, O.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: substantiate the results of theoretical and practical investigations aimed at improving the health of students. Material: the study involved 187 children including 103 boys and 84 girls aged 7-10 years. Results: through a rapid assessment of physical health it was found that pupils of primary school age have an average level of the functional state of the organism, with a minimum resistance to risk factors (chronic non-infective diseases, etc.). For the first time, a technique for determining the level of adaptation and reserve capacity of school students proposed by Ukrainian hygienists was used in physical culture and sports practice. Conclusions: the technique reveals strain in adaptation mechanisms that corresponds to donozological condition. An idea is proposed that Nordic walking, through the positive impact on the body of aerobic mode of energy supply, is able to increase the reserve-adaptive capabilities of primary school students by improvement of their health as well as to solve the problems of health formation and health care in the physical education of youth.